The Effectiveness of Information and Communication Technology as a Learning Medium for Islamic Education and Character Building (A Study at a State Senior High School in Poso) - Fandi Nur Cahyo Santoso; Nurdin, Nurdin; Ahmad syahid; Riskiana, Riskiana (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2025)
This study examines the integration of Information and Communication Technology (ICT) as a learning medium for Islamic Education and Character Building at Poso 1 Public Senior High School. In the digital era, ICT has become an essential tool for creating innovative and interactive learning environments. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. Data analysis follows the Miles and Huberman model, involving data reduction, display, and conclusion drawing. The findings indicate that ICT significantly enhances student engagement and understanding through digital platforms and multimedia presentations. While challenges such as limited hardware and unstable internet connectivity persist, the overall implementation has proven effective. Beyond cognitive gains, the integration of ICT fosters positive character development and critical thinking aligned with Islamic values. This study concludes that technology integration is a strategic necessity to address modern educational challenges while maintaining the core principles of religious education.